The influence of the SSB’s characteristics toward Sharia compliance of Islamic banks - Rifqi Muhammad (Taylor & Francis Group, 2021)
This paper aims to examine the influence of SSBs’ characteristics toward Sharia compliance of Islamic banks in Asia and Gulf Cooperation Council (GCC). An epistemological model of the unity of knowledge was applied to determine the contribution of SSB to the Sharia compliance of Islamic banks that can create the well-being. The samples in this study are Islamic banks in Asia and Gulf Cooperation Countries (GCC) for the period of 2010 to 2018. The characteristics of SSB consist of the number of SSB members, cross membership, level of education, expertise, remuneration and rotation. This study analyzes the data using data panel regression with software of reviews. This study finds that SSB size has negative influence while education and expertise have positive influence toward sharia compliance of Islamic banks. Meanwhile, cross membership, remuneration and rotation of SSB members do not influence sharia compliance of Islamic banks. In general, the role of SSB in carrying out the function of creating well-being for the community has not been carried out optimally. This paper would benefit to formulate the development of Sharia compliance parameter and to increase the roles of SSB in optimizing the operation of Islamic banks particularly in fulfilling Sharia principles. The samples in this study are from countries that have contribution in the infrastructures of Islamic financial institutions around the world. The result may become the model for strengthening the role of SSB in other countries.